Hubungan Perilaku Picky Eater dengan Status Gizi Remaja di Smp Negeri 20 Semarang - Mardika Jihan Novita; Indra Tri Astuti; Herry Susanto (Journal of Health, Medical, and Psychological Studies, 2025)
This study aimed to analyze the relationship between picky eating behavior and nutritional status among adolescents at SMP Negeri 20 Semarang. A cross-sectional design was conducted involving 264 students aged 12–15 years. Picky eating behavior and nutritional status were assessed using structured questionnaires and anthropometric measurements. Data were analyzed using Spearman correlation tests due to non-normal data distribution. The results showed that 62.1% of respondents were classified as picky eaters, while 59.1% had abnormal nutritional status, including underweight, overweight, and obesity. Statistical analysis revealed a significant relationship between picky eating behavior and nutritional status (p = 0.003) with a negative correlation coefficient (r = −0.183), indicating that higher picky eating behavior tended to be associated with lower nutritional status. Adolescents with picky eating behavior were more likely to experience inadequate nutrient intake, which may affect growth and development during a critical period of adolescence. Although the strength of the relationship was weak, picky eating behavior remains an important behavioral factor influencing adolescent nutritional status. Comprehensive nutritional education and behavioral interventions are needed to improve dietary quality and prevent long-term nutritional problems among adolescents.